Competency-Based Approach In Lifelong Learning: As A Factor In Preparing Students For Life - Jabbor Eshbekovich Usarov (Euro Asian Journal Publishing, 2023)
The importance of ensuring continuity in education is determined by the content of education, based on a competency-based approach in preparing logically, creatively thinking, socially active graduates for life. The article discusses the formation of subject competencies in the process of teaching physics in general education institutions and its importance in lifelong education
Keywords: Continuing education; educational cluster; educational subjects